Christianity, generation and narrative religious conversion and change in Sidama, Ethiopia, 1974-2012 - Egeland, Erik. (Sweden. : Uppsala university Uppsala, 2016)
This study presents narratives concerning religious conversion and change in Evangelical-Pentecostal Christian communities in the Sidama zone, Southern Ethiopia. The study is based on narrative data collected through field research, which mainly focuses on the period 19742012. This data is supplemented with previous research and unpublished sources.
Keywords: Religion and sociology; Christianity and culture ; -- Christianity and politics ; -- Church and the world; Christian youth